М
Молодежь
К
Компьютеры-и-электроника
Д
Дом-и-сад
С
Стиль-и-уход-за-собой
П
Праздники-и-традиции
Т
Транспорт
П
Путешествия
С
Семейная-жизнь
Ф
Философия-и-религия
Б
Без категории
М
Мир-работы
Х
Хобби-и-рукоделие
И
Искусство-и-развлечения
В
Взаимоотношения
З
Здоровье
К
Кулинария-и-гостеприимство
Ф
Финансы-и-бизнес
П
Питомцы-и-животные
О
Образование
О
Образование-и-коммуникации
irinamyn1
irinamyn1
02.02.2020 14:16 •  Алгебра

Рациональные уравнения 9 класс​

👇
Ответ:

Объяснение:

\displaystyle\\1)\frac{x+4}{x+1}-\frac{10}{x^2-1}=\frac{10}{3} ;ODZ:x\neq -1;x\neq 1\\\\\\\frac{x+4}{x+1}-\frac{10}{(x-1)(x+1)}=\frac{10}{3}\\\\\\\frac{3(x+4)(x-1)-30-10(x^2-1)}{3(x+1)(x-1)}=0\\\\\\3(x^2+4x-x-4)-30-10x^2+10=0\\\\3x^2+9x-12-20-10x^2=0\\\\=-7x^2+9x-32=0\\\\D=81-4*7*32=81-896=-815

ответ: ∅

---------------------------------------------------------------------

\displaystyle\\2)\frac{x}{x+4}}+\frac{5}{x-4} =\frac{32}{x^2-16} ;ODZ:x\neq 4;x\neq -4\\\\\\\frac{x(x-4)+5(x+4)-32}{x^2-16} =0\\\\\\x^2-4x+5x+20-32=0\\\\x^2+x-12=0\\\\D=1+4*12=49=7^2\\\\x_1=(-1-7)/2=-4;ne\ udowl.odz\\\\x_2=(-1+7)/2=3\\\\Otvet:x=3\\\\

-----------------------------------------------------------------------

\displaystyle\\3)\frac{x-3}{x+2} +\frac{x-3}{2-x} =\frac{20}{x^2-4};ODZ:x\neq -2;x\neq 2\\\\\\\frac{(x-3)(x-2)-(x-3)(x+2)-20}{x^2-4}=0\\\\\\x^2-3x-2x+6-x^2+3x-2x+6-20=0\\\\-4x-8=0\\\\x=-2;ne\ udowl.odz\\

ответ: ∅

--------------------------------------------------------------------

\displaystyle\\4)\frac{x+5}{x-2}+\frac{x-4}{x+1}=\frac{21}{(x-2)(x+1)} ;ODZ:x\neq 2;x\neq -1\\\\\\(x+5)(x+1)+(x-4)(x-2)-21=0\\\\x^2+5x+x+5+x^2-4x-2x+8-21=0\\\\2x^2-8=0\\\\x^2=4\\\\x_1=2;ne\ udowl.odz\\\\x_2=-2\\\\Otvet:x=-2

4,4(24 оценок)
Открыть все ответы
Ответ:
ania51
ania51
02.02.2020

ответ:

объяснение:

f(x)=x³-27x

1)  f `(x)=(x³-27x)`=3x²-27=3(x²-9)=3(x-3)(x+3)

2) f `(x)=0 при  3(x-3)(x+3)=0

                            x=3   v   x=-3

                +                       -                     +

-

                ↑                       ↓                       ↑

f(x) - возрастает на (-∞; -3)u(3; +∞)

f(x)- убывает на (-3; 3)

4,4(44 оценок)
Ответ:
Linkin251
Linkin251
02.02.2020
5-3х           2х              5-3х+2х               5-х                       1       +      = = = 25-х(2)       25-х(2)          25-х(2)                 (5-х)*(5+х)         5+х           прих= -1,5         1                     1  =     = 1: 7/2=1*2/7=2/7 5+(-1,5)               3,5    
4,4(94 оценок)
Это интересно:
logo
Вход Регистрация
Что ты хочешь узнать?
Спроси Mozg
Открыть лучший ответ